Aspetos sintáticos das interrogativas-Q do Português de Moçambique - Chutumiá, Danifo Ismael (elingUP: Revista Eletrónica de Linguística dos Estudantes da Universidade do Porto, 2017)
The aim of this study is to analyse the syntax of wh interrogatives of Mozambican Portuguese (MP), comparing them with those of European Portuguese (EP) and Brazilian Portuguese (BP). The data suggest that there are a few similarities in the whinterrogatives of the three varieties of Portuguese. Notwithstanding these similarities, there are in MP interrogatives with the constituent wh on an intermediate position, which seems to be a particularity of this variety, revealing an innovative change in relation to the other two standards of Portuguese language.